Analisis Fraud Hexagon dan Tata Kelola Perusahaan Atas Adanya Kecurangan Dalam Laporan Keuangan - M. Rizkiawan; Subagio Subagio (Integritas: Jurnal Antikorupsi, 2022)
This research examines the impact of corporate governance and the Fraud Hexagon on possible financial statement fraud. The Fraud Hexagon is a fraud theory proposed by Vousinas in 2019, which is a development of the previous fraud theory. This research uses two independent variables, including the Fraud Hexagon, which consists of six factors and corporate governance. The likelihood of fraud in financial statements is also a dependent variable in this research. State-owned businesses (BUMN) and related entities that are listed on the Indonesia Stock Exchange (BEI) serve as the research object. To analyse the data for this research, logistic regression was used. According to the test results, opportunity and rationalisation have a very significant impact on the possibility of financial statement fraud, as do pressure and capability and collusion testing. However, arrogance and corporate governance have no significant impact on financial statement fraud.